Identifying cognitive aspects to improve business process reengineering - Martín, Adriana Elba (2004)
Knowledge-intensive processes are widely used to recover from errors, handle exceptional cases and complaints, and to improve or adapt a process itself. In this context, evolved Business-Process Reengineering (BPR) techniques are changing to give some answers to this reality. In this paper, we identify some cognitive aspects used by traditional and recent reengineering models. We provide a framework highlighting how cognitive aspects might improve reengineering through knowledge and perception modelling.